ASSOCIATION OF ANTENATAL DEPRESSION AND HOUSEHOLD FOOD INSECURITY AMONG PREGNANT WOMEN: A CROSS-SECTIONAL STUDY FROM SLUMS OF LAHORE - Ayyub, Hafsa; Sarfraz, Mariyam; Mir, Khizran; Salam, Fakiha tus (Journal of Ayub Medical College Abbottabad, 2018)
Background: Pregnant women are more likely to develop antenatal depression due to multiple factors including sickness and death of close family member, unwanted pregnancy, unplanned pregnancy, economic and relationship difficulties. Food insecurity is a major issue in low resource settings, especially in developing countries. Malnourishment in pregnant women along with antenatal depression can lead to adverse effect on growth of foetus and can lead to adverse pregnancy outcomes. The aim of this study was to determine an association between food insecurity and antenatal depression among pregnant women living in slum settlements of Lahore. Method: A community based, cross-sectional study was conducted in slum settlements of district Lahore, with a sample of 367 pregnant women. Antenatal depression and household food insecurity was measured using Edinburgh Postnatal Depression Scale (EPDS) and Household food insecurity access scale (HFIAS). Data was entered and analysed in SPSS-20.0. Chi-square and multivariate logistic regression analysis was used to estimate effect of food insecurity on antenatal depression among pregnant women. Results: Prevalence of antenatal depression was 39.5% among pregnant women. Majority of the sample, i.e., 46% were food insecure. In an adjusted model, multivariate logistic regression showed existence of strong association between food insecurity and antenatal depression (AOR=2.58, 95%, CI: 1.64-4.075) in women surveyed. Conclusion: Study results show strong association between food insecurity and antenatal depression. Findings also suggest the need of an effective intervention at community level to combat food insecurity and antenatal depression in marginalized populations. Keywords: Food insecurity; Antenatal; Slums; Nutrition; Pregnancy; Developing Country; Pakistan